Analytical Model for Sandwich-Lithiation in Hollow Amorphous Silicon Nano-Anodes Coated on Carbon Nanofibers. Issue 2 (1st January 2016) - Li, Xiangdong; Fang, Qihong; Li, Jia; Wu, Hong; Liu, Youwen; Wen, Pihua
Abstract : This paper describes an elastic-plastic deformation model considering both concurrent propagation of lithiation fronts and lithiation induced volume expansion at lithiation fronts to investigate the sandwich-lithiation mechanism in a hollow amorphous silicon (a-Si) nano-anode coated on carbon nanofiber (CNF), focusing on the distribution of lithiation induced stress field and its effect on the driving forces for lithiation fronts, fracture and interfacial debonding of a-Si/CNF composite structure. An a-Si shell and two fully lithiated shells are separated by the opposite movement of two atomically sharp lithiation fronts during sandwich-lithiation. The results show that the driving forces are governed by sandwich-lithiation induced stresses. Lithiation reaction resistance at the lithiation front which propagates toward the center of the hollow silicon nanowire is lower and thus results in the thicker lithiation layer at the external surface. The smaller the outer radius of the hollow silicon nanowire is, the lower resistances the lithiation fronts undergo. The thickness of the CNF should be in an appropriate range provided that the mechanical strength is satisfied. It is hoped that these quantitative results can provide an insight into sandwich-lithiation reaction, optimal design and failure modes of a-Si/CNF composite structures for high performance lithium-ion batteries.